Relationship Between Serum Ferritin Level and Hba1c in Bangladeshi Type 2 Diabetic Patients - Khondker, Farhana; Roy, Manindra Nath; Saha, Purnima Rani; Huq, Rubena; Ahmed, Rumana; Biswas, Sumona (Anwer Khan Modern Medical College Journal, 2018)
Background: Diabetes mellitus (DM) type 2 is one of the most common endocrine disorders affecting more than 135 million people in the world. The etiology of the disease is not fully understood, but recently subclinical hemochromatosis has been considered as one of the probable causes of DM. This study was carried out to examine the relationship between serum ferritin as a marker of iron overload with DM and HbA1c. Materials & Method: This study was conducted in the Biochemistry department of Sir Salimullah Medical College, Dhaka; over a period of 18 months from July 2013 to December 2014. In this case control study, 46 patients with type 2 diabetes were taken as case, who were referred to theoutpatient department of "Ibrahim General Hospital & Diabetic care & Educational Center"(DCEC). 46 normal individuals were included as the control group, who were matched with the case group regarding age, sex, BMI and Hb%. Ferritin, hemoglobin, HbA1c and fasting plasma sugar were measured in blood samples. Exclusion criteria included anaemia, or any other disease or drug that could affect ferritin levels. Result: Results were analyzed statistically by Chi-square test, Student's t-test, Pearson correlation coefficient test and Odds ratio.Mean serum ferritin was significantly higher in diabetics than in the control group (197.97±75.99 µgm/L vs. 64.24±27.83 µgm/L, p<0.001). There was significant positive correlation between serum ferritin and HbA1cin diabetic patients (p<0.001). In this study, OR of 11.64 was also found. Conclusion: Serum ferritin is positively correlated with type 2 Diabetes Mellitus. And this may be an important and independent predictor for development of diabetes mellitus. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 29-33